Integrating Ethical Values and New Public Services: Strengthening Reform and Anti-Corruption in Indonesia - Yacob Noho Nani; Juriko Abdussamad; Sri Yulianty Mozin; Rustam Tohopi (Universitas Muhammadiyah Yogyakarta, 2025)
This article offers an integrated model of ethical values ​​and NPS principles in overcoming corruption in the context of reform in Indonesia. The research findings identify several forms of deviation of the value system, such as abuse of authority, deviation of norms, discriminatory practices, and intervention of power in bureaucratic practices, which have become major issues for the potential for corruption that has taken root in the bureaucratic culture in Indonesia. On the other hand, the contribution of the NPS paradigm related to service values, transparency, participation and accountability is also inadequate in strengthening the governance system. Therefore, this study recommends ethical values, about the importance of honesty, integrity and ethics, prioritizing public interests as an alternative to strengthening the reform system in overcoming corruption. A systematic review and inclusive criteria showed several weaknesses of the reform system and the inadequacy of NPS in strengthening governance to overcome corruption. However, empirical facts show that post-reform corruption has occurred more widely in almost all lines of bureaucracy and public sector organizations. This study offers the I-EdMP model as an analytical tool for strengthening the NPS value system and principles as a moderating factor in overcoming various forms of corruption violations. This model was developed as an alternative that clarifies ethical obligations and violations to strengthen reform by integrating public ethical values ​​into the reform system.